Numerical study of radiation and fuel-air unmixedness on the performance of a dry low NOx combustor - Wiranegara, Raditya Yudha; Igie, Uyioghosa; Ghali, Pierre; Zhao, Rang; Abbott, David; Hamilton, Richard (American Society of Mechanical Engineers (ASME), 2022)
The development of gas turbine combustors is expected to consider the effects of radiation heat transfer in modelling. However, this is not always the case in many studies that neglect this for adiabatic conditions. The effect of radiation is substantiated here, concerning the impact on the performance, mainly the emissions. Also, the fuel-air unmixedness (mixing quality) influenced by the combustor design and operational settings has been investigated with regards to the emissions. The work was conducted with a Mitsubishi-type Dry Low NOx combustor developed and validated against experimental data. This 3D computational fluid dynamics study was implemented using Reynolds-Averaged Navier Stokes simulation and the Radiative Transfer Equation model. It shows that NO, CO and combustor outlet temperature reduces when the radiative effect is considered. The reductions are 17.6% and below 1% for the others respectively. Thus, indicating a significant effect on NO. For unmixedness across the combustor in a non-reacting simulation, the mixing quality shows a direct relationship with the Turbulence Kinetic Energy (TKE) in the reacting case. The most significant improvements in unmixedness are shown around the main burner. Also, the baseload shows better mixing, higher TKE and lower emissions (particularly NO) at the combustor outlet, compared to part-load.
Keywords: combustion; computational fluid dynamics